Respons Positif Teologi Kristen Protestan terhadap Sekularisasi Di Dunia Barat Modern - Mohammad Nuh Hasan (Refleksi, 2022)
This article discusses how Protestant Christian theology responds to the strengthening of the secularization phenomenon. The positive response with various styles of theological reflection illustrates that the Protestant Christian theology figures above, starting from Karl Barth, Rudolf Bultmann, Dietrich Bonhoeffer and Paul Tillich, are the efforts of theologians to try to bridge the gap or gap in cultural rationality between the cultures of the classical era in where the texts of the scriptures were written with modern Western culture today. These theologians include those who give a positive response in dealing with the phenomenon of secularization in the West. However, their response actually has a style that is more or less different in their way of thinking. Although Karl Barth proposed an advanced mode of reflection, he was still bound by his orthodoxy, so that he was nicknamed "neo-orthodox". Rudolf Bultmann was more liberal with his "Demythologized" ideas. Dietrich Bonhoeffer had already begun to advocate a secular Christian interpretation, and Paul Tillich had further advocated a correlational theological approach to religion and culture. Next, Harvey Cox further tries to construct a more comprehensive reflection of Secularization theology, that the secular world is a world in which Christians are mature people. As a sign, Jesus' death on the cross is a symbol, that he has left his absoluteness, his supernatural being, to become a secular "God".